P351 Genetic recombination between the main human skin commensal fungus, Malassezia restricta, and M. globosa using an Agrobacterium tumefaciens-mediated gene transfer system. (20th September 2022) - Cho, Otomi; Matsumoto, Yasuhiko; Yamada, Tsuyoshi; Sugita, Takashi
Abstract: Poster session 3, September 23, 2022, 12:30 PM - 1:30 PM:   Objects: Malassezia restricta and M. globosa cause or exacerbate Malassezia -associated skin, seborrheic, and atopic dermatitis, as well as pityriasis versicolor, but the virulence factors remain unclear because between-species genetic recombination has not yet been achieved. We built an Agrobacterium tumefaciens-mediated gene transfer (ATMT) system that generated gene-knockout mutants of both Malassezia species. Materials and Methods: The binary vector pAg1-Δfkb1::NAT1 was introduced into M. restricta CBS 7877 and M. globosa CBS 7966 via ATMT; FKB1 was replaced. Then, FKB1 was re-introduced into the mutants to counteract the deficiencies. Results and Discussion: The medium acetosyringone concentration and temperature, as well as the co-cultivation ratios of A. tumefaciens and the Malassezia strains, affected recombination efficacy. We generated a mutant of the FKB1 gene (which encodes the FKBP12 protein that binds to the calcineurin inhibitor tacrolimus). Wild-type M. restricta and M. globosa were tacrolimus-sensitive, while the FKB1 mutants were tacrolimus-resistant; drug susceptibility was restored by reintroducing FKB1. Conclusion: Studies on recombination between M. restricta and M. globosa will aid elucidation of the molecular mechanisms underlying Malassezia -associated dermatitis.